PENGARUH KEBIJAKAN PEMERINTAH TERHADAP KESEJAHTERAAN PELAKU EKONOMI UBI KAYU DI PROVINSI LAMPUNG - Septaria Indah Sari; R. Hanung Ismono; Indah Nurmayasari (Lampung University, 2013)
This research aims to analyze the impacts of interest rates and urea fertilizer price policies on the welfare ofcassava economic stakeholders in Lampung Province. This study uses the secondary data 1990-2010analyzed by using two stages least squares (2SLS) model, and simulated based on changes in policies. Thewelfare of cassava economic stakeholders is based on the net surplus between producer surplus andconsumer surplus. The simulation showed that the 10 % increase in interest rate caused the decrease in netsurplus of 36.25 percent. The 10 % decrease in interest rate increased the net surplus by 10.18 percent. The15 % rise in urea fertilizer price caused the decrease in net surplus by 7.69 percent. Moreover, thecombination of 15 % increase in urea fertilizer price and 10 % decrease in interest rate caused the increasein net surplus by 325.17 percent.